2020
DOI: 10.3390/ma13204596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Parameters on Cutting Metallic Materials

Abstract: This experimental study investigated the effect of laser parameters on the machining of SS41 and SUS304. The metallic materials play an important role in engineering applications. They are widely used in high-tech industries such as aerospace, automotive, and architecture. Due to the development of technology and high-tech industrialization, the various processing technologies are being developed with the requirement of high precision. However, the conventional cutting process is difficult to meet high precisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the past few years, researchers studied the possibility of cutting with a CO 2 laser of different materials such as methyl polymethacrylate [16], Al 6061-T6 alloy [17], 304 stainless steel [18], AISI 1045 austenitic steel [19], AlSI 304, AlMg3 and St37-2 [20], SS41 and SUS304 [21], pure titanium and Ti-6Al-4V titanium alloys [22], Ti6Al4V alloy [23] and Nickel-based super alloys Nimonic 263 [24].…”
Section: Synthesis Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, researchers studied the possibility of cutting with a CO 2 laser of different materials such as methyl polymethacrylate [16], Al 6061-T6 alloy [17], 304 stainless steel [18], AISI 1045 austenitic steel [19], AlSI 304, AlMg3 and St37-2 [20], SS41 and SUS304 [21], pure titanium and Ti-6Al-4V titanium alloys [22], Ti6Al4V alloy [23] and Nickel-based super alloys Nimonic 263 [24].…”
Section: Synthesis Of Literaturementioning
confidence: 99%
“…Son et al studied the cutting width for sheet metal SS41 and SUS 304. Through the ANOVA procedure, the authors demonstrated that the significant indicators are the cutting speed and the laser power [21]. Savanth et al used a YAG laser to apply a layer of Colmonoy-5 to the surface of carbon steel plates.…”
Section: Synthesis Of Literaturementioning
confidence: 99%
“…The success of oxygen or nitrogen cutting depends on the focus distance, which needs to be well adjusted to the upper surface of the metal sheet. On Figure 3 could be seen when cutting with oxygen, the focus must be above the upper surface of the sheet, and when cutting with nitrogen, the focus must be on or slightly above the lower surface of the sheet [8,9].…”
Section: Parameters and Properties Of Cutting With Auxiliary Gasesmentioning
confidence: 99%
“…Selecting the most suitable parameter settings becomes one of the most practically essential tasks to improve product quality and productivity simultaneously in laser cutting. e effect of laser control factors on the material should be treated as an essential issue in order to increase product quality and productivity [1]. Pradhan and Biswas research examined the impacts of the power factor, including discharge current and applied voltage, on the surface roughness of metallic inputs [2].…”
Section: Introductionmentioning
confidence: 99%